EVALUATION OF THE IMPLEMENTATION OF PROCESS STANDARDS IN THE 2013 CURRICULUM IN BIOLOGY LEARNING AT SENIOR HIGH SCHOOLS IN KUNINGAN REGENCY - Junaedi, Edi; Putra, Angga Permana; Abidin, Zaenal (Universitas Lancang Kuning, 2025)
This study aims to evaluate the implementation of process standards in the 2013 Curriculum in Biology learning at the senior high school level in Kuningan Regency. This research employs a qualitative descriptive approach with a purposive sampling technique, involving six schools with one Biology teacher representing each school as respondents. Data were collected through observations, interviews, documentation, and questionnaires. The findings indicate that most schools have developed lesson plans (RPP) following Circular Letter No. 14 of 2019, yet the actual implementation in the learning process does not fully align with the initial planning. The scientific approach has not been optimally applied, particularly in questioning and developing students' critical thinking skills. The primary challenges faced by teachers include limited learning media, difficulties in implementing scientific-based methods, and low student engagement in online learning. Additionally, the introductory and closing activities need improvement, particularly in terms of student motivation, reflection, and feedback. Therefore, strengthening scientific-based learning strategies, utilizing technology more effectively, and providing teacher training are essential to enhancing the effectiveness of Biology learning under the 2013 Curriculum